1987
DOI: 10.1136/jnnp.50.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Clinical neurological examination, neuropsychology, electroencephalography and computed tomographic head scanning in active amateur boxers.

Abstract: SUMMARY Twenty active amateur boxers were studied seeking evidence of neurological dysfunction and, if present, the best method for detecting it. Seven of these boxers had an abnormal clinical neurological examination, eight an abnormal EEG and nine of 15 examined had abnormal neuropsychometry. The CT scan was abnormal in only one. An abnormal clinical examination correlated significantly (p < 005) with an increasing number of fights, and an abnormal EEG with decreasing age (p < 0O05). In several of the neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 8 publications
1
21
1
1
Order By: Relevance
“…Concussion may, at least temporarily, 4-8 and perhaps permanently, [9][10][11][12][13][14] impair aspects of cognition. It seems imperative therefore that attempts should be made to prevent, or at least minimise, their occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concussion may, at least temporarily, 4-8 and perhaps permanently, [9][10][11][12][13][14] impair aspects of cognition. It seems imperative therefore that attempts should be made to prevent, or at least minimise, their occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] It has been suggested that repeated concussion may irreversibly affect attention [9][10][11][12][13][14] and memory. [11][12][13][14] However, prospective studies are lacking and this assertion therefore remains controversial. Regardless of their potential long term effects, rugby related concussions are an important health concern, and effective methods of prevention need to be developed.…”
mentioning
confidence: 99%
“…Studies without a control group12-'4 19 have sought to compare results with normal population standards. Despite the methodological weakness of such a design the results suggest similar tendencies and themes.…”
mentioning
confidence: 99%
“…De lá para cá, estudos mais sofisticados vêm sendo realizados na tentativa de elucidar os mecanismos fisiopatológicos envolvidos nesses quadros. Estudos de neuroimagem estrutural têm mostrado presença de atrofia cerebral generalizada 3,[8][9][10][11] , alterações na substância branca e áreas focais de contusão 12 em populações de ex-pugilistas. Essas alterações cerebrais estruturais estão associadas a alterações neuropsiquiátricas, ao nú-mero de lutas e a nocautes sofridos, mostrando um efeito acumulativo dos traumatismos cerebrais.…”
Section: Relato De Casounclassified